Library: a complex social organization - Sánchez Vanderkast, Egbert J. (2014)
The library as a social organization is affected in their organizational levels as it depends in most cases of an institution with a mission and vision itself. Simultaneously is governed by LIS theoretical and methodological principles that make an information system. At another level, and extra-social elements intrasocietal one way or another not only modify the library work, but also library development plans, the particular programs to be implemented in library systems and internal procedures in order to have an organization dynamic and functional, to provide access to information that is demanded by users. Achieving a communion between the various levels of organization and between the above elements, it becomes a complex organization. The objective pursued in this paper is to review what the library features that make it a complex organization; what are the interrelationships of the library and extrasocial intrasocietal identified elements; and how social capital is built in different nuclei of society through access to information.